Nyomárkay István: Rövid horvát és szerb nyelvtörténet (Kurze Geschichte des Kroatischen und des Serbischen): Budapest: ELTE Szláv Filológiai Tanszék, 2007. Opera Slavica Budapestinensia. Linguae Slavicae. S. 292. - Vig, István (Slavia Centralis, 2020)
Nyomárkay István: Rövid horvát és szerb nyelvtörténet (A Brief History of Croatian and Serbian)The author of the article presents the first history of Croatian and Serbian, written in Hungarian; its author is István Nyomárkay.
Keywords: István Nyomárkay; history of Croatian and Serbian; Rövid horvát és szerb nyelvtörténet; history of language; monograph; book review